LEGAL BASIS OF ACQUITTAL IN BANKING CREDIT CORRUPTION: PANGKALPINANG DISTRICT COURT CASE - Agustiani; Muhamad Adystia Sunggara (Awang Long Law Review, 2026)
This research aims to analyze the legal considerations of the Panel of Judges in acquitting the defendant, Ardian Hendri Prasetyo, in a corruption case involving bank credit distribution at Bank Rakyat Indonesia (BRI) Pangkalpinang Branch. It also examines the consistency of the verdict with the principles of criminal law and the anti-corruption legal framework in Indonesia. This study uses a normative juridical method with a case study approach and court decision analysis. The data were obtained through literature review and official court documents. The findings indicate that the Panel of Judges found the elements of corruption, particularly abuse of authority and state financial loss, not legally and convincingly proven. The acquittal also reflects the application of the in dubio pro reo principle and procedural criminal law. This study contributes to a better understanding of evidentiary law in banking corruption cases and highlights the importance of accurate legal interpretation of criminal elements.